Impact of Oil Price Fluctuations on Economic Growth in Saudi Arabia: Evidence from a Nonlinear ARDL Approach - Elhassan, Tomader (International Journal of Energy Economics and Policy, 2021)
This study examined the asymmetric impact of oil price on economic growth in Saudi Arabia in 1970–2020 using annual data from the Saudi Central Bank and the World Bank. Applying a nonlinear autoregressive distributed lag model, this research focuses on the impact of oil price fluctuations, separating oil prices into negative and positive shocks. The results revealed the statistical significance of positive shocks on the partial sum of oil prices in both the short- and long term, whereas negative shocks had long term, but not short term, statistical significance on economic growth. The effect of positive shocks in oil price was greater than the effect of negative shocks in the long- and short term, and negative shocks were not an area of concern for the Saudi economy. Moreover, the coefficient of error correction terms (âˆ’1) had a negative and statistically significant value, indicating that any shock in the past years was corrected within one year at a rate of 54%. This study provides practical insights supporting policymakers' development of sound policies and useful findings and approaches for economists and energy researchers. The promotion of advanced technology policies to reduce the economic risks of oil price fluctuations is essential. Keywords: Asymmetric, Oil Price Fluctuations, Economic Growth, NARDL, Saudi Arabia JEL Classifications: C32, E32, E32, F43, O47, Q43 DOI: https://doi.org/10.32479/ijeep.11574